Research on Optimality of Beamforming in MIMO Model to Improve SER in Multipath Mobile Transmission Environment - Tran, Hoai Trung (Old Journal, 2018)
Some papers are researching on how to optimize the beam weighs in generally. They discover beam patterns are related with upper bound of SER and can allocate power to these beams. The environment is used to illustrate these beams are Ricean and Rayleigh distributed. However, in multipath mobile environments, how they are applied in the transmit beams needs to be made clear. This paper concentrates on use of the multipath mobile channel matrix of MIMO to form the beams along with the physical paths at the transmitter. The paper also uses power allocation for these beams on principle of " water filling", the gain of path is better, more transmit power is assigned to the path. The simulation can show the SER is improved if using more beams for more paths and also the optimal power allocation is giving the lower SER compared with the case using equal power allocation to all paths.